Taxonomic revision of critical taxa of Elwendia (Umbelliferae-Apioideae) from Tajikistan and neighbouring countries, with descriptions of three new species from the Pamir-Alay and distributional novelties - Kljuykov, Eugene V.; Lazkov, Georgii A.; Degtjareva, Galina V.; Zakharova, Ekaterina A.; Ukrainskaja, Uljana A.; Lyskov, Dmitry F.; Samigullin, Tahir H. (Phytotaxa, 2022)
A study based on morphological and molecular (ITS/ETS nrDNA) data presents a taxonomic revision of the genus Elwendia in Tajikistan and neighbouring countries with a special attention to the E. kuhitangi – E. salsa complex. As a result, three new species of Elwendia from Tajikistan are described: E. darwasica, E. schistosa, and E. varsobica. Elwendia varsobica differs from all of these species by broad ovate-lanceolate sheaths of stem leaves and dorsally compressed mericarps. Elwendia darwasica and E. schistosa differ from E. kuhitangi and E. salsa by erect or slightly spreading styles of fruits. Improved morphological descriptions of E. kuhitangi and E. lindbergii as well as a new identification key for all Elwendia species known from Tajikistan and adjacent regions are provided. The distribution of E. lindbergii and E. capusii is expanded: E. lindbergii is reported for the first time from Tajikistan and E. capusii from Afghanistan.